2021
DOI: 10.1016/j.scitotenv.2020.143875
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of chemical contaminants on degradable and non-degradable microplastics: Recent progress and research trends

Abstract: HIGHLIGHTS• Microplastics (MPs) serve as vectors of chemical contaminants.• The sorption capacity of MPs depends on mechanisms and factors.• The sorption capacity of degradable MPs is similar or higher than nondegradable MPs.• Future research must focus on elucidating the full potential of degradable MPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(87 citation statements)
references
References 171 publications
0
69
0
1
Order By: Relevance
“…Sorption process usually stem from van der Waals interaction when they cannot be explained by either electrostatic interaction or hydrophobic interaction . The sorption of chemical contaminants by aliphatic polymeric sorbents such as polyethylene microplastics and polyvinyl chloride takes place through van der Waals interactions (Hüffer and Hofmann, 2016;Fred-Ahmadu et al, 2020a;Torres et al, 2021).…”
Section: Van Der Waals Forcementioning
confidence: 99%
“…Sorption process usually stem from van der Waals interaction when they cannot be explained by either electrostatic interaction or hydrophobic interaction . The sorption of chemical contaminants by aliphatic polymeric sorbents such as polyethylene microplastics and polyvinyl chloride takes place through van der Waals interactions (Hüffer and Hofmann, 2016;Fred-Ahmadu et al, 2020a;Torres et al, 2021).…”
Section: Van Der Waals Forcementioning
confidence: 99%
“…Thus, MPs did not influence the uptake and toxicity of silver (Ag) in zebrafish [61] while an antagonistic interaction with cadmium (Cd) was observed in the common goby juveniles [62]. In this regard, the ability of contaminants to be adsorbed to plastics may depend on the plastic's features and the type of contaminant [63], which directly influences its combined toxicity. Other studies carried out with cell lines have revealed that NPs seem to reduce the cytotoxicity of pharmaceuticals [40,48], whereas they failed to alter the toxicity of BaP and 3-nitrobenzanthrone (3-NBA) [64].…”
Section: The Presence Of Nanoplastics Increases the Toxicity Of Metalsmentioning
confidence: 99%
“…In general, the adsorption mechanism between MPs and heavy metals can be generally described by electrostatic interactions, van der Waals forces, and π-π interactions (Fu et al, 2020;Lin et al, 2021;Torres et al, 2021). It was shown that all MPs have a pH point of zero charge (pHpzc) around 3, which implies that in the natural aqueous environment, MPs should carry a negative charge on their surface (Lin et al, 2021).…”
Section: Adsorption Kinetics and Isotherms Of Heavy Metals On Mpsmentioning
confidence: 99%
“…Compared to electrostatic interactions, van der Waals forces and π-π interactions play a relatively small role. However, they can further promote the sorption capacity (Torres et al, 2021). Their occurrence depends on the polymer type; e.g., PE (aliphatic polymer) exhibits van der Waals interactions, while PS (aromatic polymer) exhibits mainly π-π interactions.…”
Section: Adsorption Kinetics and Isotherms Of Heavy Metals On Mpsmentioning
confidence: 99%